Tumor del saco vitelino de testículo en un niño de dos años de edad con criptorquidia izquierda: reporte de un caso - Carcasi Laura, Edgar Alfredo (2021)
Testicular cancer is a very rare malignant tumor in prepubescent males younger than 15-year-old with an incidence of 1/1 000 000. Testicular yolk sac tumor is the most common type of testicular germ cell tumor (TCGT) in children younger than 2-year-old. Clinical case: Child of 2-year-old and five months with cryptorchidism left, which presented, six months ago, progressive increase of a tumor located in the entire left groin; characterized by being of hard consistency, painless and show no discoloration changes in the overlying skin. Results: In the auxiliary examinations, the ultrasound showed: large solid mass, ovoid, heterogeneous echogenicity and multiple anemic cavities. The only tumor marker with an increase was Alpha-fetoprotein (AFP): 12 845.00 ng/mL. The presumptive diagnosis was of malignant testicular tumor until proven otherwise. Radical inguinal orchiectomy is performed with satisfactory postsurgical evolution. Conclusion: Malignant testicular tumor in prepubescent males younger than 15-year-old is very rare, and the most common type of TCGT in children younger than 2-yearold is yolk sac tumor.